2012
DOI: 10.1166/jnn.2012.5374
|View full text |Cite
|
Sign up to set email alerts
|

Direct-Patterning of Porphyrin Dot Arrays and Lines Using Electrohydrodynamic Jet Printing

Abstract: In this research, we have fabricated micron-sized patterns of porphyrins on silicon substrates using an electrohydrodynamic (EHD) jet printing technique. Optical and fluorescence microscopies have been used to examine the shape and fluorescence property of porphyrin patterns. The morphology of the porphyrin patterns printed with variously formulated porphyrin inks and the effects of applied voltage, working distance, and substrate properties on the morphology of patterns were investigated using scanning electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Moreover, e-jet printing is a typical technique that is affected by coupled multi-physics [ 19 ]. The formation, flying, and deposition of the jet have significant impacts on printing resolution and positioning accuracy [ 20 ]. The processes are influenced by interactions of electric field force, gravity, capillary force, viscous force, air resistance, and surface tension.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, e-jet printing is a typical technique that is affected by coupled multi-physics [ 19 ]. The formation, flying, and deposition of the jet have significant impacts on printing resolution and positioning accuracy [ 20 ]. The processes are influenced by interactions of electric field force, gravity, capillary force, viscous force, air resistance, and surface tension.…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have reported the construction and biomedical applications of porphyrin-liposomes by the functionalization of porphyrins with lipids via esterification or amidation reactions. It is a well established fact that porphyrins generally conjugate with amphiphilic lipids with a high loading content [58][59][60][61]. Because of the amphiphilicity of porphyrin lipids, they could directly self-assemble into porphyrin liposomes in physiological condition with the porphyrin motifs at the walls.…”
Section: Porphyrinic Amphiphilesmentioning
confidence: 99%
“…[31][32][33] These allotropes exhibit exciting structural and functional properties that can be converted into several intriguing applications. Briefly, carbon nanomaterials exhibit extraordinary electrical, 34 thermal, mechanical, 35,36 chemical, 37,38 optical, 39 nuclear (magnetic) 40 and biological properties. [41][42][43] All these properties in one material were merely impossible to imagine few years back but now it has become a reality.…”
Section: Carbon Nanoallotropes (Cnas)mentioning
confidence: 99%